1995
DOI: 10.1002/tera.1420510603
|View full text |Cite
|
Sign up to set email alerts
|

Defining the susceptible period of developmental toxicity for the AT1‐selective angiotensin II receptor antagonist Losartan in rats

Abstract: Previous developmental and reproductive toxicity studies conducted in rats with Losartan, a potent AT1 subtype selective angiotensin II receptor antagonist, noted treatment-related effects on the pups of dams treated beyond the second trimester through lactation, as demonstrated by increases in pre- and postweaning pup deaths and decreased pup body weights [Spence et al. (1995) Teratology 51:000-000]. The studies presented here were designed to define the critical period for the induction of neonatal toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 25 publications
4
27
0
2
Order By: Relevance
“…We selected this dose of losartan based on previous studies that showed developmental toxicity was evident in the newborns from mothers that received doses ≥ 100 mg/kg/day. 25,26 At this dose, losartan was detected in breast milk in a concentration close to 50% of the maternal serum in 75% of dams. The combination of losartan with tempol was based on a study by Dobrian et al 27 Tempol is a small molecule that is able to cross biological membranes, and the treatment of rats with this compound was able to decrease both cytosolic and mitochondrial ROS production.…”
Section: Animals and Experimental Protocolsmentioning
confidence: 91%
“…We selected this dose of losartan based on previous studies that showed developmental toxicity was evident in the newborns from mothers that received doses ≥ 100 mg/kg/day. 25,26 At this dose, losartan was detected in breast milk in a concentration close to 50% of the maternal serum in 75% of dams. The combination of losartan with tempol was based on a study by Dobrian et al 27 Tempol is a small molecule that is able to cross biological membranes, and the treatment of rats with this compound was able to decrease both cytosolic and mitochondrial ROS production.…”
Section: Animals and Experimental Protocolsmentioning
confidence: 91%
“…Spence et al (34,35) have shown in experimental studies that maternal treatment with losartan during late gestation and lactation is associated with lower pup body weights and higher pup mortality rates during the preweaning/postweaning periods, as well as irreversible histopathologic renal abnormalities in the F1 generation. Morphological renal findings, such as dilation of the renal pelvis, edema of the renal papilla, medial hypertrophy of intracortical arterioles, chronic renal inflammation, and irregular scarring of the renal parenchyma, have been described in rats.…”
Section: Renal Development In Offspring Of Mothers That Received Angimentioning
confidence: 99%
“…Losartan was administered daily in drinking water during lactation. The dose was based on previous work [20] indicating that developmental toxicity was evident in newborns from dams that received doses ≥100 mg/kg/day. Losartan was detected in the milk of dams that received 100 mg/kg/day of this drug [21].…”
Section: Animals and Methodsmentioning
confidence: 99%